1982
DOI: 10.2337/diab.31.1.s54
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications

Abstract: Background: microRNAs (miRNA, miR) are thought to interact with multiple mRNAs resulting in either translational repression or degradation which is involved in the EMT process. Since miRNAs distributed with tissue specificity, the role of miRNAs in peritoneal fibrosis remains unknown. Our unpressed data showed that expression of miRNA589 was notably decreased in HPMCs isolated from patients undergoing long-term continuous ambulatory peritoneal dialysis (CAPD).Objective: To determine if miRNA589 regulates the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Our observation of elevated levels of plasma lipids in the diabetic hamsters as compared with the non-diabetic controls agree with the previous reports by Gerristen and Dulin (1967), and Chobanian et al (1974Chobanian et al ( , 1982, who found hyperlipidemia in the diabetic hamsters in the Upjohn colony.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our observation of elevated levels of plasma lipids in the diabetic hamsters as compared with the non-diabetic controls agree with the previous reports by Gerristen and Dulin (1967), and Chobanian et al (1974Chobanian et al ( , 1982, who found hyperlipidemia in the diabetic hamsters in the Upjohn colony.…”
Section: Discussionsupporting
confidence: 83%
“…Chobanian et al (1982) reported that the major increases occurred in the d < 1.006 fraction in the diabetic hamsters. However, other characterization of the lipoproteins had not been performed in the hamsters in the Upjohn colony partly because plasma volume obtained was too small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both the American Diabetes Association and the Juvenile Diabetes Foundation International made recommendations for the development of such models over a decade ago (37,38), the lack of appropriate animal models is still recognized (5,39). Diabetes appears spontaneously in numerous animal species, and several genetic models have been developed in rodents (40 -42).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative, chronic effects of this metabolic disease lead eventually to debilitating functional and morphological alterations, such as nephro-, neuro-, and retino-pathy [2]. Cardiovascular responses to diabetes include an increase in plasma lipoproteins, atherosclerosis, hypertension, and cardiomyopathy [3]. In large animals such as dogs and primates, including humans, diabetic retinopathy can progress to the proliferative stage, which is associated with neovascularization of retinal vessels, vitreous hemorrhage, retinal detachment, and visual impairment [4,5].…”
mentioning
confidence: 99%